Impact of COVID-19 lockdown on match-activity and physical performance in professional football referees - Moreno-Perez, Victor; Martín-Sánchez, María Luisa; Coso, Juan; Luis Felipe, Jose; Courel-Ibañez, Javier; Sánchez-Sánchez, Javier (Biology of Sport, 2021)
To investigate the effect of COVID-19 lockdown on match-play metrics in professional football referees during official matches of the Spanish professional leagues. Forty-two professional football referees from the First (n = 20) and Second Division (n = 22) were monitored during 564 official games using Global Positioning System (GPS) technology. Data of matches before lockdown were compared to matches after resumption of the competition. Compared to pre-lockdown, in the referees of the First Division there was a decrease in the total running distance and the distance covered at all speed thresholds > 6 km ·h-1 after lockdown (P < .05). In the Second Division referees, the post-lockdown measurement only showed a decrease in the running distance at 21–24 km·h-1 (P < .05), with no changes in the other speed thresholds. The postlockdown measurement showed an increased distance covered at < 6 km·h-1 and the number of accelerations for both First and Second Division referees (P < .05). Referees’ match activity was reduced due to the COVID-19 lockdown, while the effect on running parameters was more pronounced in First Division referees.